THE ECONOMY IN CRISIS AND GLOBAL IMBALANCE: AN ESSAY ON STRUCTURAL CAUSES - Vieira, Euripedes Falcão; Vieira, Marcelo Milano Falcão (Pensamento & Realidade, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> This essay is the result of considerations on determining factors of the financial crash that have started in 2008. It caused negative effects throughout the economic field and in the social order of the countries participating in the global order. It was not, therefore, a crisis of the production sector of the economy but rather of financial speculation within the economic field, fast spreading, to a greater or lesser degree, to all structures and organizations addressing production and social well-being. Bubbles or any other names are only a play on words in the deviations of financial activity. The global economy is moved by the credit system, which feeds the resources for productive investments. Purposeful deviations in this sector affect the entire economic system. The analysis in this essay looks to focus on the cause of the global financial imbalance, still far from solution, outside the interpretations normally made after the produced effects. The regulatory benchmarks adopted in the 21st-century global economy are not appropriate since they were set for another past economic reality. With no new regulations, principally global, new outbreaks of financial crises will periodically occur to disturb the economic and social order of countries individually or in economic blocs.